PENERAPAN METODE PROTOTYPE PADA APLIKASI PENJADWALAN KERJA DAN KEGIATAN KARYAWAN BERBASIS PWA - Abdul Rokhim; Muhammad Abdul Rizki (SPIRIT, 2021)
Abstract : Work and events scheduling is one of the most important parts in the sustainability of the production process in the company. One company from Pasuruan Regency which is engaged in soft drink production, still uses Microsoft Excel software in managing data that has several. Therefore we need a system that can manage schedules more efficiently. In building this system, using a website platform and using the prototype method as its approach. The Prototoype method is used with the aim of providing a common perception and understanding between researchers and clients of the basic process of the system to be built so that later it is expected to produce an appropriate system. In this application has several main features, for example, the push notification feature. This push notification is aimed at employees making it easier for employees to get up-to-date schedule information.Keywords: Work and events scheduling, prototype, push notification